Husbands' Wages and Married Women's Labor Supply in Urban China - Mengbing Zhu; Yi Li; Chunbing Xing (Institute of Labor Economics (IZA), 2023)
This study examines the impact of husbands' wages on their wives' labor force participation rates and hours worked in urban China from 1995 to 2018. We find that an increase in husbands' wages reduces the labor force participation rate of married women with similar education levels. Controlling for gender identity—in particular, an aversion to the wife earning more than her husband—strengthens the income effect of husbands' wages. The labor supply effect of husbands' wages is more significant for younger and less-educated women and those with more children. The employed women's hours worked are negatively correlated with their husbands' wages, which is more significant for married women of older cohorts and with more children. This study helps us better understand the trend of the female labor supply in urban China. It sheds light on the impact of gender identity, welfare inequalities across families, and the well-being of households facing economic shocks.
Keywords: D13; D31; J16; J21; 330; husbands' wages; female labor force participation; hours worked; gender identity